Concrete desorption isotherms and permeability determination: effects of the sample geometry. Issue 1 (2nd January 2017) - Sémété, P.; Février, B.; Le Pape, Y.; Delorme, J.; Sanahuja, J.; Legrix, A.
Abstract : The isotherm sorption curve is a first-order parameter used in the Finite Element modelling of concrete moisture transport, shrinkage and creep behaviour. An original experimental campaign was developed by EDF R&D in order to characterise the first desorption isotherm at room temperature of a laboratory concrete. Long-term drying tests were carried out on three sample geometries: radial and axial one-dimensional drying on thin discs and multi-dimensional drying on representative elementary volumes (REV), in order to evaluate the possibility of accelerating the tests. Porosity, densities and mass loss curves are measured and the first-desorption isotherms obtained for the three different configurations are compared. Several analyses of these results are proposed including the assessment of a criterion for the determination of the moisture content final balance (estimation of the asymptotic mass loss) and the back analysis of equivalent permeability. The tests results show the significant time gain using thin (2.5 mm) concrete half samples drying in radial direction compared to the REV samples.